(searching for shadows) - Baughman, Paul (My University, 2016)
This thesis outlines the art practice of artist Paul Baughman. His work investigates the role of the individual as it relates to agency, power, and change, in the context of contemporary society. His research systematically looks for unseen potential hidden in the role of the individual, and the systems that house this individual, that are currently blanketed by shadows.
Thesis (Master's)--University of Washington, 2016-06
Keywords: art; individual; Paul Baughman; shadows; society; systems; Fine arts; fine arts